Herbicides to Kill Invasive Trees in Home Landscapes - Kenneth A. Langeland (EDIS, 2006)
Homeowners can play an important role in the fight against invasive plant species. SS-AGR-127, a 5-page illustrated fact sheet by K. A. Langeland, describes control methods that can be used by homeowners to remove invasive plant species from their property and cautions about pesticide licensing and regulations. Includes a table of herbicides used for control of invasive plant species. Published by the UF Department of Agronomy, July 2006.